SISTEM PENUNJANG DALAM PENGAMBILAN KEPUTUSAN PEMBERIAN REWARD DOSEN TERBAIK MENGGUNAKAN METODE TOPSIS - Hayati, Nova; Syaputra, Aldo Eko; Eirlangga, Yofhanda Septi (J-Icon : Jurnal Komputer dan Informatika, 2023)
Lecturers are professional teaching staff who provide all their knowledge and loyalty through teaching students, research and community service. To increase the performance and loyalty of lecturers to tertiary institutions, this is done by giving rewards to the best lecturers. In making the decision to give rewards to lecturers, there are several steps and criteria that must be met, because the large number of lecturers and criteria causes the assessment team to experience difficulties in processing the criteria data and lecturer data who are entitled to the reward, so a method is needed that is implemented into a computerized system that will facilitate the work of the assessment team in data processing and the resulting data to be accurate and reliable. The data applied in this research is data from permanent university lecturers and the conditions set by the university. The purpose of this research is to maximize the performance of the assessment team in processing criteria data and university permanent lecturers to get the best lecturers who are entitled to receive rewards using the TOPSIS method. The decision in determining the alternative to giving rewards to the best lecturers, by selecting 3 lecturers as recipients of the best lecturer rewards as an alternative is the result of this study. From these results, there are influential criteria, namely Research, Teaching, and Attendance.